Associations of anthropometry since birth with sagittal posture at age 7 in a prospective birth cohort: the Generation XXI Study. Issue 7 (26th July 2017) - Araújo, Fábio A; Lucas, Raquel; Simpkin, Andrew J; Heron, Jon; Alegrete, Nuno; Tilling, Kate; Howe, Laura D; Barros, Henrique
Abstract : Objectives: Adult sagittal posture is established during childhood and adolescence. A flattened or hypercurved spine is associated with poorer musculoskeletal health in adulthood. Although anthropometry from birth onwards is expected to be a key influence on sagittal posture design, this has never been assessed during childhood. Our aim was to estimate the association between body size throughout childhood with sagittal postural patterns at age 7. Design: Prospective cohort study. Setting and participants: A subsample of 1029 girls and 1101 boys taking part in the 7-year-old follow-up of the birth cohort Generation XXI (Porto, Portugal) was included. We assessed the associations between anthropometric measurements (weight, height and body mass index) at birth, 4 and 7 years of age and postural patterns at age 7. Postural patterns were defined using latent profile analysis, a probabilistic model-based technique which allows for simultaneously including anthropometrics as predictors of latent profiles by means of logistic regression. Results: Postural patterns identified were sway, flat and "neutral to hyperlordotic"in girls, and "sway to neutral", flat and hyperlordotic in boys; with flat and hyperlordotic postures representing a straightened and a rounded spine, respectively. In both girls and boys, higher weight was associated with lower odds of a flat pattern compared with a sway/"sway to neutral"pattern, with stronger associations at older ages: for example, ORs were 0.68 (95% CI 0.53 to 0.88) per SD increase in birth weight and 0.36 (95% CI 0.19 to 0.68) per SD increase in weight at age 7 in girls, with similar findings in boys. Boys with higher ponderal index at birth were more frequently assigned to the hyperlordotic pattern (OR=1.44 per SD; p=0.043). Conclusions: Our findings support a prospective sculpting role of body size and therefore of load on musculoskeletal spinopelvic structures, with stronger associations as children get older.